2020
DOI: 10.2218/gtopdb/f16/2020.5
|View full text |Cite
|
Sign up to set email alerts
|

Class A Orphans (version 2020.5) in the IUPHAR/BPS Guide to Pharmacology Database

Abstract: Table 1 lists a number of putative GPCRs identified by NC-IUPHAR [194], for which preliminary evidence for an endogenous ligand has been published, or for which there exists a potential link to a disease, or disorder. These GPCRs have recently been reviewed in detail [150]. The GPCRs in Table 1 are all Class A, rhodopsin-like GPCRs. Class A orphan GPCRs not listed in Table 1 are putative GPCRs with as-yet unidentified endogenous ligands.Table 1: Class A orphan GPCRs with putative endogenous ligands�… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“… ,, Their potencies can vary from a few to one hundred micromolar range in various assay platforms (Table ). Thus, MCFAs have been proposed to be the endogenous ligands of GPR84, but GPR84 has not been officially deorphanized as a free fatty acid receptor because the concentration of MCFA under physiological conditions is only around its EC 50 for GPR84 activation and is greatly affected by diets. Analysis of fasting blood of healthy adult volunteers ( n = 43) showed that C10 concentration is between 2 and 18 μM, and dodecanoic acid ( C12 ) concentration is between 6 and 90 μM .…”
Section: Agonistsmentioning
confidence: 99%
“… ,, Their potencies can vary from a few to one hundred micromolar range in various assay platforms (Table ). Thus, MCFAs have been proposed to be the endogenous ligands of GPR84, but GPR84 has not been officially deorphanized as a free fatty acid receptor because the concentration of MCFA under physiological conditions is only around its EC 50 for GPR84 activation and is greatly affected by diets. Analysis of fasting blood of healthy adult volunteers ( n = 43) showed that C10 concentration is between 2 and 18 μM, and dodecanoic acid ( C12 ) concentration is between 6 and 90 μM .…”
Section: Agonistsmentioning
confidence: 99%
“…Additionally, evidence of ligand binding in a given tissue via in vitro binding assays, functional assays, and anatomic data is crucial [ 58 ]. For MRGPR, at least one of the criteria mentioned is lacking; however, in a recent report in 2019 by IUPHAR/BPS, MRGPRX2 is listed as a class A orphan GPCR for which preliminary evidence for an endogenous ligand and potential disease link has been published [ 65 ].…”
Section: Pharmacology Of Mas-related G Protein-coupled Receptors X 2 (Mrgprx2)mentioning
confidence: 99%
“…Characterization of orphan receptors may lead to uncovering physiological functions, thus connecting them to diseases. GPR39 is among the class A orphan receptors [2]. Several endogenous agonists have been proposed, including the element zinc [3,4], yet the classification of GPR39 as a zinc receptor remains contentious.…”
Section: Introductionmentioning
confidence: 99%